Thea Stilton And The Dragon's Code - Thea Stilton & Geronimo Stilton
Geronimo's adventurous sister Thea takes center stage in this super special that's packed with mystery, adventure, and friendship! When Geronimo's sister, Thea, is invited to teach a journalism class at a college on Mouse Island, she has no idea that she's going to be called on to help solve a mystery. But when a student disappears, it's up to Thea and five of her students to find out what happened. A nail-biting mystery ensues, complete with secret passages, underground tunnels, and more than a few surprises along the way. Readers will love following the clues to help Thea and her new friends through their first adventure together!